Efficacy of a classical antiobesity Unani pharmacopial formulation (Safoof-e-Muhazzil) in systolic and diastolic blood pressure: A randomized, open-labeled, controlled clinical study - Asim Ali Khan; Umar Jahangir; Farhan Jalees; Prem Kapoor; Shaista Urooj (Wolters Kluwer Medknow Publications, 2013)
The aim of this study is to evaluate the efficacy of a Unani formulation in hypertension. A total of 90 patients with total cholesterol level of more than 220 mg/dl with associated conditions were included in this study. A total of 30 patients having a mean systolic blood pressure (BP) of 133.86 mmHg comprising Group A received Unani formulation Safoof-e-Muhazzil (SM) in its classical powder form in the dose of 5 g twice a day orally. Group B comprising of 30 patients with a mean systolic BP of 133.13 mmHg received same drug, but in compressed tablet form in the same dosage, whereas, 30 patients comprising Group C with a mean systolic BP of 129.45 mmHg, received Atorvastatin 10 mg as a standard control. Patients were evaluated on each follow-up at 2 nd , 4 th and 6 th week. The mean systolic BP in Group A and B before treatment was 133.86 ± 3.028 mmHg and 133.13 ± 2.852 mmHg, which significantly decreased to 119.33 ± 1.922 mmHg (P < 0.001) and 119 ± 1.760 mmHg (P < 0.001) respectively. In the control Group C before treatment BP was 129.45 ± 2.499 mmHg and after treatment it significantly decreased to 124.34 ± 1.794 mmHg (P < 0.01). The percentage change after treatment was 10.85%, 10.61% and 3.94% respectively in each group. Mean diastolic BP in Group A and B before treatment was 85.06 ± 2.11 mmHg and 84.56 ± 1.5 mmHg, which significantly decreased to 79.06 ± 1.56 mmHg (P < 0.001) and 79.96 ± 1.15 mmHg (P < 0.001) respectively, BP before treatment in Group C was 83.23 ± 1.588 mmHg, which was decreased to 124.34 ± 1.794 mmHg (P < 0.01). The study results indicate that the test drug was quite effective in reducing both systolic as well as diastolic BP.